2022
DOI: 10.3390/antibiotics11081055
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Allergy De-Labeling: A Pathway against Antibiotic Resistance

Abstract: Antibiotics are one of the most frequently prescribed drugs. Unfortunately, they also are the most common cause for self-reported drug allergy, limiting the use of effective therapies. However, evidence shows that more than 90% of patients labeled as allergic to antibiotics are not allergic. Importantly, the label of antibiotic allergy, whether real or not, constitutes a major public health problem as it directly impacts antimicrobial stewardship: it has been associated with broad-spectrum antibiotic use, ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 123 publications
(157 reference statements)
0
13
0
Order By: Relevance
“…[7][8][9][10][11][12][13] From a community point of view, the use of second-line antibiotics may facilitate the emergence of bacterial resistance and increase healthcare costs. 14 Many adults with a penicillin allergy label acquired it in childhood, so its pernicious effects are prolonged throughout life. 15 Most reactions associated with the use of BLA appear during the course of treatment of an infectious disease, and they are usually mild and limited to the skin, in the form of a maculopapular rash or urticaria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] From a community point of view, the use of second-line antibiotics may facilitate the emergence of bacterial resistance and increase healthcare costs. 14 Many adults with a penicillin allergy label acquired it in childhood, so its pernicious effects are prolonged throughout life. 15 Most reactions associated with the use of BLA appear during the course of treatment of an infectious disease, and they are usually mild and limited to the skin, in the form of a maculopapular rash or urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…Children labeled as allergic to BLA are at risk of receiving less appropriate antibiotics and as a result, suffering side effects and having longer hospital stays 7–13 . From a community point of view, the use of second‐line antibiotics may facilitate the emergence of bacterial resistance and increase healthcare costs 14 . Many adults with a penicillin allergy label acquired it in childhood, so its pernicious effects are prolonged throughout life 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Juhlin et al in 1978 first suggested that basophil degranulation could be used in clinical allergy diagnoses (26). The use of basophil activation testing (BAT) in penicillin allergy diagnosis has not yet become common practice (27). The latest EAACI position paper on improving diagnosis of beta-lactam hypersensitivity from 2020 (16) recommends in vitro testing such as BAT or sIgE, prior toin vivo testing in high risk patients, or instead of ST when the latter is contra indicated or not possible.…”
Section: Introductionmentioning
confidence: 99%
“…This mislabeling triggers socioeconomic and health problems, such as antibiotic resistance, necessitating delabeling initiatives in antibiotic stewardship programs. 2,3 Delabeling initiatives encompass both in vivo and in vitro testing approaches. However, the routine clinical application of these methods is constrained by the time-consuming and risky nature of in vivo tests and the low sensitivity (approximately 81% false negatives) exhibited by current in vitro techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, accurate clinical and analytical assessment reveals a significant misclassification of individuals as allergic, leading to unnecessary prescription of alternative antibiotics. This mislabeling triggers socioeconomic and health problems, such as antibiotic resistance, necessitating delabeling initiatives in antibiotic stewardship programs. , …”
Section: Introductionmentioning
confidence: 99%